‘Trying to open the doors’: The co-creation of digital resources for disadvantaged primary school pupils - Thiele, Tamara; Homer, Damien (International Journal for Students as Partners, 2023)
This article explores the use of co-creation as an approach for involving university students in the development of educational initiatives for widening participation (WP) in higher education (HE) during the COVID-19 pandemic. At present, research and guidance looking at how co-creation practices can enable the production of such initiatives within HE is highly limited, which can deter others from employing this approach. To this end, we provide a case study of a WP project called Topic in a Box that involved staff and students working together to produce digital learning material for primary schools and students over several months. Through the use of semi-structured interviews with nine students, this research provides insight into the steps that were taken to develop the project, capturing the motivations, benefits and challenges of co-creation practice from a student perspective. We argue that this mode of co-creation should be used to a greater extent across the university sector and in recognition that university students have much to offer in terms of widening access to university.